Symptomatic meningothelial hamartoma associated with nevus sebaceus - Jessica Biagiotti; Colleen Beatty; Zachary Zinn; Aaron Mason (Elsevier, 2020)
We describe the third reported case of a symptomatic meningothelial hamartoma associated with nevus sebaceus. A 2-year-old male presented with a congenital, painful, enlarging parietal scalp nodule arising adjacent to a nevus sebaceus, and associated with an ipsilateral capillary malformation in the distribution of the first branch of the fifth cranial nerve. Meningothelial hamartomas are rare and clinically lack any defining diagnostic features. On histology, the pseudoinfiltrative pattern and presence of anastomosing channels raise concern for vascular proliferations. The symptomatic nature of the nodule and the potential for intracranial extension warranted imaging workup. Histologic evaluation ultimately led to a diagnosis of meningothelial hamartoma. This case highlights the novelty and nuances in the work-up, management and treatment of a symptomatic meningothelial hamartoma when it presents in association with a nevus sebaceus and possible Sturge Weber Syndrome.